Pengaruh Faktor-Faktor Pelaksanaan PP 46 Tahun 2013 Terhadap Kepatuhan Wajib Pajak UMKM (Studi Kasus UMKM Pusat Grosir Tanah Abang Jakarta Pusat) - Endro Andayani (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
This research is an annual background by implementation of PP 46, 2013 to facilitate SMEs Taxpayer with omzet of less than  4,8 M. This research, especialy analyzed the factors’s that effects the complienceness of the implementation of PP 46,2013 on SMEs Taxpayer with variables such as perception of justice, tax knowledge of PP 46, 2013, Tax  Administration, Benefits, Sanctions and Goverment socialization, partially or simultaneously. This research using  quantitative appoach, The data used are primary data, collected using quetionnaires fill by respondents, chosen using non probabilty sampling, and sampling technique by purposive sampling.Data analyzed using multiple linear regression. The population of this study are small business and Enterpreneurships in wholesale center Tanah Abang with annual gross income less than 4,8 M , criteria by gender, education backgrounds, business longevity, incorporated or have a NPWP (Identification Legal Entity Tax Payer Goverment) and monthly average sales . The results of this study indicates that perception of justice of PP 46, 2013, Knowledge of PP 46, 2013, Administration, Benefit, Sanctions and Socialization, takes effect on SMEs tax payer compliance in the wholesale center Tanah Abang . The samples used in this study were 86 respondentsThe results of this  indicates that perception of justice of PP 46, 2013, Knowledge of PP 46, 2013, Administration, Benefit, Sanctions and Socialization, takes effect on SMEs tax payer compliance in the wholesale center Tanah Abang either partially or simultaneously.